2013
DOI: 10.1016/j.jspr.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of psocids (Psocoptera) in temperature gradients in stored wheat

Abstract: a b s t r a c tPsocids have become important pests of stored products during the last two decades, but little is known about their behavior or ecology. We examined distribution of Liposcelis bostrychophila Badonnel (Psocoptera: Liposcelididae), Liposcelis entomophila (Enderlein), and Liposcelis paeta (Pearman), three of the main psocid pests of stored grain throughout the grain growing regions of the world, in temperature gradients of 20 e24 C, 20 e30 C, and 20 e42 C in small bulks of wheat to determine their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Different temperatures and moisture contents in wheat create different relative humidities. This may impact their movement and preferred location in grain stored in bins or in different temperature (Throne and Flinn, 2013) and moisture gradients as demonstrated in this study. This research shows how psocids respond to different moisture gradients in grain, which can help to improve sampling methods and to make better pest management decisions.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Different temperatures and moisture contents in wheat create different relative humidities. This may impact their movement and preferred location in grain stored in bins or in different temperature (Throne and Flinn, 2013) and moisture gradients as demonstrated in this study. This research shows how psocids respond to different moisture gradients in grain, which can help to improve sampling methods and to make better pest management decisions.…”
Section: Discussionmentioning
confidence: 86%
“…The distribution of psocids in different moisture gradients was determined using a circular metal arena (60 cm in diameter by 9 cm in height) Hagstrum, 1998, 2011). The arena was insulated with an attached base and a removable lid (2 cm thick wood and 3.5 cm thick insulating foam on the outside) (Throne and Flinn, 2013). The arena had a removable metal divider that partitioned it into three rings (outer, middle, and inner).…”
Section: Moisture Gradientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Opit et al (2009) observed that populations of psocids in steel bins were more abundant at the center of the bin during the fall where temperature and grain moisture content were higher that in other parts of the bin. In laboratory tests, L. bostrychophila responded to temperature gradients (Throne and Flinn 2013) and moisture gradients (Diaz-Montano et al 2014a), with a preference for the warmest and highest moisture regions. However, how stored-product psocids respond to light conditions has not been investigated.…”
Section: Introductionmentioning
confidence: 99%